Beneficial effects of deep sea fish oil on diabetic mice neurological injury - Qiao, Z.; Chen, Y.; Zhang, Y.; Niu, Q. (Cellular and Molecular Biology, 2017)
Deep sea fish oil mainly includes polyunsaturated fatty acid, which is usually used as health products and applied for prevention of cardiovascular and cerebrovascular diseases. However, there are only a few studies investigating the diabetes induced nerve injury till now. We established the diabetic model by using the 8-week old inbred male mice, and assumed that fish oil had a certain therapeutic effect on related neurosensory impairment and oxidative stress. Mice were divided into group A (diabetic mice induced by streptozotocin (STZ) and treated with fish oil), group B (diabetic mice) and group C (normal mice, without STZ treatment). The memory and exploration ability were evaluated and oxidation status of brain tissue was detected. Results indicated that memory and exploration ability of fish oil group A was significantly improved compared to diabetic group B (P<0.05), and equal to group C. The malondialdehyde (MDA) level of fish oil group A was decreased significantly and antioxidant level was increased significantly compared to diabetic group B (P<0.05), and equal to group C. In conclusion, deep sea fish oil could be used as auxiliary health care products, which plays important role in preventing and treating implications of nerve lesion impairment induced by diabetes mellitus.